“Greater Than They” (Luke 9:46). On the Reception of a Markan Doublet in Luke - GRÜNSTÄUDL, Wolfgang (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
The most widely accepted example of a Markan doublet is the logion on greatness in Mark 9:35//10:43–44. Both halves of this “sayings doublet” are themselves part of two episodes on quarrels among Jesus’ disciples (cf. Mark 9:33–37; 10:35–45) which build something like a “narrative doublet” in Mark. Assuming Luke’s redaction of Mark, the present study analyzes the fate of this striking Markan doublet(s) within the Lukan framework in order to shed some new light at Luke’s redactional activity as well as his theological agenda. After a brief look at Luke’s incorporation of Mark 9:33–37 and Mark 10:35–45, this paper highlights some unexpected interpretative challenges in Luke 9:46–48 and argues for a fresh reading of Luke 9:46 (based on a very old proposal) that may offer a solution to the riddles of Luke’s redaction of Mark 9:33–37.